Defending the jury : crime, community, and the Constitution / Laura I Appleman (Willamette University College of Law). - Appleman, Laura I. (Cambridge University Press, 2015)
This book sets forth a new approach to twenty-first-century criminal justice and punishment, one that fully involves the community, providing a better way to make our criminal process more transparent and inclusive. Using the prism of the Sixth Amendment community jury trial, this book offers fresh and much-needed ways to incorporate the citizenry into the procedures of criminal justice, thereby resulting in greater investment and satisfaction in the system. It exposes the various challenges the American criminal justice system faces because of its ongoing failure to integrate the community's voice. Ultimately, the people's right to participate in the criminal justice system through the criminal jury - a right that is all too often overlooked - is essential to truly legitimizing the criminal process and ensuring its democratic nature.